Fronteiras e divisas: qualidade urbana no distrito da Vila Mariana em São Paulo - Galvão, Thaty Tamara Baldini (2021)
This work investigates the relationship between, on one hand, the interface between buildings and streets and, on the other, the way in which the public uses the city space and the possibility the latter offers to generate encounters – seen as essential qualities of a city. It does so through an investigation of how much human activity in public spaces bordering real estate developments depends on the architecture that results from the parameters applied to developed plots. This work’s main objective is to assess the likely impact of the new regulatory frameworks implemented by the city of São Paulo (Act 16.050/2014, Act 16.402/2016 and Act 16.642/2017) on the improvements to the urban landscape and to public spaces. Given existing attempts by the city government to increase demographic density and encourage the mixed use (commercial and residential) of developments, this work assumes that such improvements seek to incentivize a greater appropriation of spaces by the public. The empirical research focuses on data collected in the São Paulo district of Vila Mariana. The work uses Sennett’s (2018) concepts of Borders and Boundaries as tools to analyze urban space. Sennett sees borders as cell membranes, i.e., structures that are simultaneously porous and resistant, and able to select what must enter and what must leave. By contrast, boundaries are similar to cell walls, i.e., watertight structures aiming to prevent foreign objects from entering the organism. The research analyzes Borders and Boundaries that remain to this day in the Vila Mariana district and looks into the consequences stemming from them for the city’s physical and social aspects. It discusses the tools seeking to improve the urban landscape included in the 2014 Strategic Masterplan (Act 16.050/2014), in the Land Plotting, Use and Occupation Act (Act 16,402/2016) and in the Building Code (Act 16.642/2017). Finally, it seeks to answer the question, “Will the Land Plotting, Use and Occupation Act produce the desired positive outcomes for the urban quality of the city of São Paulo?”